2019
DOI: 10.1002/cem.3163
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of stabilized nitrocellulose during artificial aging: Spectroscopy methods coupled with principal component analysis

Abstract: In this work, Fourier transform infrared spectroscopy (FTIR) and X-ray powder diffraction (XRD) were selected as reliable, fast, and nondestructive techniques to assess their potentialities for characterization and discrimination of nitrocellulose (NC)-based formulations containing different kinds of stabilizers and subjected to accelerated aging. Preliminary results based on visual comparison of the spectra point out that spectra obtained by both spectroscopic techniques were useful for a rapid detection of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
27
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 65 publications
(82 reference statements)
4
27
0
Order By: Relevance
“…According to these results, it can be concluded that the NC2 and MCCN1 synthesized from cellulose and microcrystalline cellulose isolated from marine POBA, respectively, were of high purity, comparable to NC1 prepared from cotton cellulose and MCCN2 produced from C‐MCC. Besides that, it is worthy to note that the FTIR spectra of the produced cellulose nitrate and MCCN are comparable with those reported in the literature …”
Section: Resultssupporting
confidence: 85%
See 4 more Smart Citations
“…According to these results, it can be concluded that the NC2 and MCCN1 synthesized from cellulose and microcrystalline cellulose isolated from marine POBA, respectively, were of high purity, comparable to NC1 prepared from cotton cellulose and MCCN2 produced from C‐MCC. Besides that, it is worthy to note that the FTIR spectra of the produced cellulose nitrate and MCCN are comparable with those reported in the literature …”
Section: Resultssupporting
confidence: 85%
“…Moreover, the absorption band at 1430–1380 cm −1 is assigned to the asymmetric and symmetric bending vibration of CH 2 group . Additionally, the bands appeared at 1080, 830, 765, and 685 cm −1 , are related to the stretching vibration of CO group, the nitrate ester (ONO 2 ) stretching vibration, and the asymmetric and symmetric deformations of the ONO 2 group . These absorption bands are associated with the typical characteristics of nitrocellulose molecule already reported .…”
Section: Resultssupporting
confidence: 62%
See 3 more Smart Citations